2020
DOI: 10.5187/jast.2020.62.3.396
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of the enhanced beef using winter mushroom juice

Abstract: This study investigated the quality properties of enhanced beef, manufactured by injecting the beef with a brine containing winter mushroom juice powder (WMJP). The enhanced beef was manufactured by injecting the eye of round with brine (15% by green weight). Four treatments consisted of control (no injection of brine) and three enhanced beef, EBS (brine containing 5 g sodium chloride per kg beef), EBW 0.2 (brine containing 5 g sodium chloride and 2 g WMJP per kg beef), and EBW 0.5 (brine containing 5 g sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, no significant differences were observed between the pH values of raw samples and cooked samples, except for the boiled samples which have a significantly higher pH value than those found in raw mushrooms. It is generally stated that the cooking process generally leads to an increase in the pH value of food due to protein unfolding, the release of basic amino acids, and the formation of certain compounds with alkaline properties (Choi et al ., 2020; Sumer & Oz, 2023). Indeed, Choi et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, no significant differences were observed between the pH values of raw samples and cooked samples, except for the boiled samples which have a significantly higher pH value than those found in raw mushrooms. It is generally stated that the cooking process generally leads to an increase in the pH value of food due to protein unfolding, the release of basic amino acids, and the formation of certain compounds with alkaline properties (Choi et al ., 2020; Sumer & Oz, 2023). Indeed, Choi et al .…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant differences in L* and a* values, except for b* value among control, BP and BFW ( Table 4 , p>0.05). Previous study reported that the lack of an effect of winter mushroom based on its white color on the color of meat products could be a suitable property as a natural ingredient for meat products ( Choe et al, 2018 ; Choi et al, 2020 ; Jo et al, 2018 ; Jo et al, 2020b ). BP had a higher b* value than control and BFW (p<0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the water retention in the meat products was improved with the addition of winter mushrooms because of high dietary fiber and pH in winter mushrooms ( Choe et al, 2018 ). Recent studies reported that winter mushroom could be a suitable alternative to phosphate in pork sausage, chicken sausage, and enhanced beef ( Choe et al, 2018 ; Choi et al, 2020 ; Jo et al, 2018 ; Jo et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GFD had a significantly lower hardness (values of 48.25 and 55.55 N) than GFT (values of 78.59 and 100.84 N) at salt levels of 1.5% and 2.5%, respectively (p<0.05, Table 3 ). The lower protein solubility of the freeze-dried pork powder might contribute to weakening the emulsion gels because solubilized proteins form a gel network through interactions with insoluble proteins, and also by holding water molecules and fat particles ( Choi et al, 2020 ; Sun and Holley, 2011 ). An increase in salt levels results in an increase in the myofibrillar protein solubility due to enhanced electrical repulsion ( Chen et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%